Spectrophotometric Determination of Paracetamol by Diazotization and Coupling Reaction with Anthranilic Acid - Abdul- Raheem, Mohammed S.; Alsamarrai, Khalaf F.; Dikran, Sarmad B. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This paper concerned with development of a spectrophotometric method for the determination of paracetamol, based on the diazotisation and coupling reaction with anthranilic acid in basic medium, to form an intense yellow coloured, water-soluble and stable azo-dye which shows a maximum absorption at 421nm. Beer’s law is obeyed over the concentration range of 1.0-10 µg/ml; with molar absorptivity of 2.1772×104 L.mol -1.cm-1 and Sandell’s sensitivity index 6.9446 µg.cm-2. The method has been applied successfully for the determination of paracetamol in pharmaceutical formulation.